Simulation based Performance Comparison & Analysis regarding Static and Mobile Throwboxes impact on Network Performance in Delay Tolerant Networks (DTNs) using ONE Simulator - Srivastava, Aprajita; Nayyar, Anand; Jain, Rachna; Nagrath, Preeti (Journal of physics. Conference series, 2018)
Delay Tolerant Network (DTN) is another category of network that lacks continuous network connectivity. Nodes are dependent on opportunistic contacts for message forwarding. Every node has a buffer space where messages are stored till the messages are forwarded to other nodes existing the network, till the message reach the destination node. Buffer space is a crucial resource in DTNs. When a buffer space becomes full, to accommodate new messages, older messages are dropped from buffer space. As nodes in DTN are subject to high data loss and intermittent connection problems. To overcome this issue, relay nodes, i.e. Throwboxes are introduced into the network. Throwboxes are tiny, inexpensive devices, acting as additional storage units for nodes to enhance the overall DTN based network performance. Throwboxes increases contact opportunities and improve over message delivery ratio. In this paper, we aim to analyze the performance of DTN network by introducing Static or Mobile throwboxes in the network in terms of Message Delivery Ratio, Latency and Contacts per hour. Extensive simulations are performed using ONE Simulator by considering both random and planned office-based scenarios. And it is observed via simulation-based results, that with introduction of Throwboxes in DTN, message delivery ratio is improvised at a whopping rate of 14%, latency is reduced by 10% and contacts per hour shows improvement by 25%.